One swallow doesn’t make a summer: reply to Kataria - Maniadis, Zacharias; Tufano, Fabio; List, John A. (Institute of Spontaneous Order Economics, 2014)
In this paper we reply to Mitesh Kataria’s comment, which criticized the simulations of Maniadis, Tufano, and List (2014, Am. Econ. Rev.104(1), 277-290). We view these simulations as a means to illustrating the fact that we economists are unaware of the value of key variables that determine the credibility of our own empirical findings. Such variables include priors (i.e., the pre-study probability that a tested phenomenon is true) and the statistical power of the empirical design. Economists should not hesitate to use Bayesian tools and meta-analysis in order to quantify what we know about these variables.